Digital participation and digital education for people with profound and multiple disabilities and complex communication needs - Keeley, Caren; Bernasconi, Tobias (Frontiers in Communication, 2023)
Digitalisation" is the buzzword of many societal as well as social changes. Participation in society is increasingly realised digitally, which is why it is important to be involved in these processes and to participate in the digital world. The UN CRPD also assigns an important role to (digital) technology as a prerequisite for inclusion and participation. Universal design, accessibility, assistive technology, and reasonable accommodation should help to avoid exclusion for people with disabilities.People with profound intellectual and multiple disabilities (PIMD), who often have complex communication needs (CCN) in addition to severe cognitive impairments, have fundamentally limited opportunities for participation. These are also visible in the context of digitalisation. At the same time, digital media also offer specific opportunities, particularly for people with PIMD and CCN. Among other things through the combined use of assistive technologies, digital media can significantly facilitate their daily lives. The present paper examines the significance, requirements and challenges as well as the potentials of digital participation and digital education in the lives of adults with PIMD and CCN and presents considerations for the design of digital education for adults. Finally, a conceptual framework for digital education for people with PIMD is presented.